واقع وسائل الدفع الإلكترونية في ظل التحول نحو الاقتصاد الرقمي في الجزائر - صيفي فوزي; صيفي، حسنــية (University Of Eloued جامعة الوادي, 2024)
هدفت الدراسة إلى إبراز أهمية وسائل الدفع الإلكتروني ودورها في تعزيز التحول نحو الاقتصاد الرقمي الذي يشهده العالم، والوقوف على واقع استخدام هذه الوسائل في الجزائر خلال الفترة 2016-2023. وخلصت الدراسة إلى أن وسائل الدفع الإلكتروني تعتبر من أهم متطلبات التحول نحو الاقتصاد الرقمي لأن لها عدة مزايا من بينها المحافظة على السيولة وتوفير السهولة والوقت والأمن وتقليص التكاليف، ولقد عرف استخدام وسائل الدفع الالكتروني تزايدا مستمرا خلال سنوات الدراسة، غير أن هذا الاستخدام لا يرقى إلى ما هو مطلوب، وذلك لضعف البنية التحتية لتكنولوجيا المعلومات والاتصال، وعدم ثقة العديد من المتعاملين الاقتصاديين في هذه الوسائل، وهو ما يتطلب إجراءات تحفيزية لدعمها وزيادة انتشارها. Abstract: The study aimed to highlight the importance of electronic payment methods and their role in promoting the transformation towards the digital economy that the world is witnessing, and to determine the reality of the use of these methods in Algeria during the period 2016-2022. The study concluded that electronic payment methods are considered one of the most important requirements for the transition to the digital economy because they have several advantages, including preserving liquidity, providing ease, time, security, and reducing costs. The use of electronic payment methods has witnessed a continuous increase during the years of study, but this use does not amount to What is required, due to the weak infrastructure of information and communication technology, and the lack of confidence of many economic operators in these means, which requires incentive measures to support them and increase their spread.
The State of Electronic Payment Methods in Light of the Shift Towards a Digital Economy in Algeria
مداخلة
Keywords: وسائل دفع إلكتروني; اقتصاد رقمي; تكنولوجيا معلومات واتصال